2017
DOI: 10.1161/circinterventions.116.004795
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stent Size Selection on Acute and Long-Term Outcomes After Drug-Eluting Stent Implantation in De Novo Coronary Lesions

Abstract: In the bare-metal stent era, numerous studies have shown a strong association between small final stent dimensions at post-deployment and in-stent restenosis at follow-up, 1-3 which led to the so-called bigger-is-better strategy for bare-metal stent optimization. After the introduction of drug-eluting stents (DES), several studies have consistently demonstrated that DES have considerably lower optimal thresholds of final stent dimensions to predict subsequent restenosis because of significant suppression of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…Furthermore, clinical evidence suggests the existence of issues after stenting, such as restenosis, stent thrombosis, and arterial injuries. Kitahara et al studied the impact of stent oversizing, concluding that aggressive oversizing may not lead to vascular injuries at the stent edge, as arteries with siginificant stent oversizing reach better apposition without increasing the amount of dissection at the stent egde. However, Chamie et al concluded that the overstretching of the arterial wall due to an oversized stent was an important factor of dissection at stent edges.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical evidence suggests the existence of issues after stenting, such as restenosis, stent thrombosis, and arterial injuries. Kitahara et al studied the impact of stent oversizing, concluding that aggressive oversizing may not lead to vascular injuries at the stent edge, as arteries with siginificant stent oversizing reach better apposition without increasing the amount of dissection at the stent egde. However, Chamie et al concluded that the overstretching of the arterial wall due to an oversized stent was an important factor of dissection at stent edges.…”
Section: Discussionmentioning
confidence: 99%
“…been reduced by the full coverage of plaque using IVUS. 5,18) It is important to note that an increase in edge residual stenosis led to an increase in the chance of restenosis in this study. Full coverage of the lesions by a postprocedural stent is essential for good outcomes, even in this era of second-generation DESs.…”
Section: Discussionmentioning
confidence: 75%
“…6) Similarly, axial geographic miss, defined as a diameter mismatch between the stent and the native arteries, may also induce mechanical stress to the wall, resulting in edge restenosis with DES. 4,5) However, axial geographic miss had a minimal influence on the outcomes of first-generation DESs in the STTLR study (a multicenter prospective study of SES). 16) These mechanical stresses may be caused by thicker struts and might be associated with a risk of angiographic and clinical restenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the minimum stent area reflecting stent expansion postimplantation is an important independent predictor of ISR and ST 15. Theoretically, three measures can be considered to achieve the largest minimum stent area or SEI possible: (1) adequate lesion preparation, (2) optimal stent/scaffold sizing and (3) appropriate postdilatation once the stent/scaffold is implanted 3 20–22…”
Section: Discussionmentioning
confidence: 99%